EFFECTS OF ELAZIG REGION WASTE BRICK AND LIMESTONE POWDER ON ENGINEERING PROPERTIES OF SELF COMPACTING MORTAR - Acikgenc, Merve; Karatas, Mehmet; Ulucan, Zulfu Cinar (Pamukkale Univ, 2013)
The aim of this study is to investigate the effects of using mineral additives on Self compacting Mortar's (SCM) strength and viscosity properties. As Self-compacting concrete (SCC) contains less coarse aggregate than conventional concrete, mortar forms the basis of the design of SCC. Therefore, this study was found to be appropriate to use mortar. In addition, the properties of SCC such as required strength, durability and workability makes a good production of concrete inevitable. While Providing this properties, it has been presented in many studies that mineral additive (silica fume, fly ash, limestone powder, blast furnace slag etc.) and certain amount of powder material requirement is essential especially in terms of workability and consistency of SCC. Furthermore, it was aimed to prevent environmental health threats by wastes released disorderly and to add new powder material to be used in SCC and finally to reduce the cost of both transport and cement by using limestone and waste brick powder. For this purpose, 23 types of mortars, in which cement was partially replaced of limestone and waste brick powder, were produced. The mini slump flow and V-funnel tests were used to assess the workability and the self compactivity properties of the fresh mortars, and the viscosity of mortars were also measured. The hardened properties of SCM specimens including the compressive strength and tensile strength in bending were investigated and all tests were performed for 3, 7, 28 and 91 days. Moreover, capillary water absorption test were performed and, total water absorption and porosity rates of all specimens were measured.
Keywords: Self compacting mortar; Limestone powder; Waste brick powder; Viscosity; Mechanical properties